Exploring how individual adaptability and hardiness predict work engagement among recruits in the Military Skills Development System (MSDS) - Nkambule, Ayanda Hellen (Stellenbosch : Stellenbosch University, 2024)
Thesis (MCom)--Stellenbosch University, 2024.